A Novel Tolerogenic Antibody Targeting Disulfide-Modified Autoantigen Effectively Prevents Type 1 Diabetes in NOD Mice - Li, Wei; Zhang, Yan; Li, Ronghui; Wang, Yang; Chen, Lan; Dai, Shaodong (Frontiers in Immunology, 2022)
Increasing evidence suggested that the islet amyloid polypeptide (IAPP) is an essential autoantigen in the pathogenesis of type 1 diabetes (T1D) in humans and non-obese diabetic (NOD) mice. A unique disulfide containing IAPP-derived peptide KS20 is one of the highly diabetogenic peptides in NOD mice. The KS20-reactive T cells, including prototypic pathogenic BDC5.2.9, accumulate in the pancreas of prediabetic and diabetic mice and contribute to disease development. We generated a monoclonal antibody (LD96.24) that interacts with IAg7-KS20 complexes with high affinity and specificity. LD96.24 recognized the IAg7-KS20 disulfide loop and blocked the interaction between IAg7-KS20 tetramers and cognate T cells but not other autoantigen-reactive T cells. The in vivo LD96.24 studies, at either early or late stages, drastically induced tolerance and delayed the onset of T1D disease in NOD mice by reducing the infiltration of not only IAPP-specific T cells but also chromogranin A and insulin-specific T cells in the pancreas, together with B cells and dendritic cells. LD96.24 can also significantly increase the ratio of Foxp3+ regulatory T cells with Interferon-gamma-secreting effector T cells. Our data suggested the important role of disulfide-modified peptides in the development of T1D. Targeting the complexes of Major histocompatibility complex (MHC)/disulfide modified antigens would influence the thiol redox balance and could be a novel immunotherapy for T1D.